Knowledge as Dominant Protective Factor against Scabies Incidence in Sonraen, East Nusa Tenggara - Wiranata, Nyoman Agung Ardi; Deo, Dwita Anastasia; Nugroho, Teguh Dwi; Handoyo, Nicholas Edwin (Jurnal Biologi Tropis, 2025)
Scabies persists as a public health challenge in resource-limited rural areas. This study aimed to analyze the association between knowledge level and personal hygiene practices with scabies incidence and to identify the dominant factor in the working area of Sonraen Health Center. A case–control study was conducted on 66 subjects (33 cases and 33 controls) from June to July 2025. Cases were selected by total sampling from medical records, while controls were chosen via simple random sampling. Data were collected using structured questionnaires and clinical observation, analyzed with the Chi-Square test and binary logistic regression. The knowledge level showed a statistically significant relationship with scabies incidence (p = 0.012). Multivariate analysis showed that respondents who had good knowledge (p = 0.013; AOR = 5.65; 95% CI: 1.14 – 27.91) and personal hygiene were not significant in the final model (p = 0.164), although respondents with fairly good hygiene had an Odds Ratio value of 3.21 95% CI: 0.96 – 10.70 with a p value = 0.058. Knowledge acts as the dominant protective factor against scabies in Sonraen. Public health interventions should prioritize contextual health education on household-based scabies prevention.